CORELATION OF SEA SURFACE TEMPERATURE AND CHLOROPHYL CONCENTRATIONS WITH PRESENCE OF DOLPHINS IN KILUAN BAY, LAMPUNG - Kusuma, Anma Hari; Efendi, Eko; Mayagues, Henky; Yudha, Indra Gumay; Hasani, Qadar (Jurnal Perikanan Unram, 2025)
Kiluan Bay is one of the marine conservation areas in Tanggamus Regency, Province of Lampung through which dolphins migrate. This research aims to analyze the relationship between the distribution of sea surface temperature and chlorophyll with the appearance of dolphins in Kiluan Bay. This research uses an exploratory survey method. The research results show that the highest appearance of dolphins was in the Transition Season I, around 117 in the temperature range of 29,44-29,88°C with a chlorophyll concentration of 0,120-0,184 mg/m³ and the lowest in the West Season was around 31 in the temperature range of 28,56-29,34°C with a chlorophyll concentration of 0,096-0,134 mg/m³. The appearance of dolphins is more strongly related to sea surface temperature than to chlorophyll concentration because dolphins do not eat phytoplankton directly where there is a time lag where increasing the chlorophyll concentration value does not immediately have an impact on increasing the intensity value of dolphin emergence, but requires some predation time.